Perbandingan Kinerja Keuangan Perusahaan Asuransi Syariah Berdasarkan Early Warning System dan Risk-Based Capital pada PT Asuransi Jiwa Syariah Jasa Mitra Abadi Tbk Sebelum dan Sesudah Go Public - Hizrina Awaliyah; Benny Barnas (Journal of Applied Islamic Economics and Finance, 2020)
The sharia insurance industry in 2019 experienced a slowdown, as seen from the indicators of assets, contributions and gross claims. In the sharia insurance industry, the only company that has gone public is PT Asuransi Jiwa Syariah Jasa Mitra Abadi Tbk. This study aims to determine how the company's financial performance is, and to find out whether there are differences in the company's financial performance before and after going public for the 2015-2019 period. The research method used is financial ratio analysis using the Early Warning System (EWS) and Risk Based Capital (RBC) methods. The data analysis method used is a comparative descriptive analysis with a quantitative approach. The results showed that the company's financial performance after going public did not improve significantly.